Manajemen Pembiayaan Bantuan Operasional Sekolah dalam Meningkatkan Mutu Pendidikan Madrasah Aliyah di Lingkungan Kantor Kementerian Agama Kota Surabaya - Setiawan, Ari Sandi; Basuki, Ismet; Roesminingsih, Erny (Lembaga Penelitian dan Pendidikan Mandala, 2021)
In the Indonesian education world system, education financing is a strategic element that will determine the attainment of the stated educational goals for registration. In other words, the quality of education practice in Indonesia is strongly influenced by the share of education financing. Because education cannot be separated from the use of funds or expenditures in the provision of education, educational institutions must prioritize the management of these costs so that they can be allocated according to their registration. This research is a qualitative descriptive study, using observation and interview methods, the data obtained to describe the process of allocating, monitoring, and evaluating education funds provided by the School Operational Assistance for the Ministry of Religion Surabaya Office to be distributed to madrasas in Surabaya. The results of this study indicate that the management of school operational assistance funding in the Ministry of Religion Office environment starting from the distribution of funding for school operational assistance funds at madrasah has been implemented as technical guidelines have been made, which in distribution must go through several stages such as making madrasah activity plans, making letters. a cooperation agreement, each distribution is carried out in two stages. Supervision of the financing of school operational assistance funds is carried out in direct and indirect ways, direct supervision is carried out to observe, inspect, check directly on work and receive reports of realization or supervision. Indirect supervision is carried out by looking at and checking again from the accountability report that has been made by the madrasah.